Relaxation dynamics in the high-frequency crystal-field spectroscopy of PrNi₅ point contacts - Balkashin, O.P.; Sukhodub, G.L.; Yanson, I.K.; Brill, T.M.; Jansen, A.G. M.; Wyder, P. (Физика низких температур, 2001)
High-frequency point-contact (PC) spectroscopy is used to investigate the relaxation processes kinetics in the intermetallic rare-earth compound PrNi₅. A difference is observed in the spectral response between the conventional low-frequency PC data and the response signal to microwave and farinfrared radiation of PrNi₅-Cu point contacts. This difference is connected with the f-shell electronic levels (CEF levels) and phonon temporal dynamics. The phonon reabsorption contribution to the spectra above the Debye energy decreases for microwave and far-infrared frequencies. However, the crystal-field contribution to the spectra at 4.2 meV is enhanced for high frequencies reflecting the relaxation processes specific for these Fermi-statistics electron excitations. The characteristic frequency for CEF-level relaxation is evaluated as ~200 GHz.